“Pink Collar Medicine”: Medical students navigating the gendered landscape of a South African medical school - Mudaly, Ronicka; van Wyk, Jacqueline (South African Journal of Higher Education, 2016)
Gendered work experiences have influenced decisions which determine career trajectories in professions in general and in the medical profession in particular. This study aims to bring to the centre the voices of medical students at a higher education institution, in order to gain a more nuanced view of intersecting influences of gendered factors on their undergraduate experiences in clinical training settings. Ninety four students who were in their final year of study at a South African medical school were purposively selected. In this inductive, qualitative approach, semi-structured, individual, face-to-face interviews were used to generate data. The recurring themes included as findings indicated students’ anxiety about safety, details of their interactions with teaching personnel and patients, and their anxiety to find a balance between responsibilities related to their work and family commitments. Recommendations include practical solutions such as the allocation of increased funding for the assurance of women students’ safety and the monitoring of defaulters who are guilty of gender discriminations in clinical settings.